REQUIREMENTS OF LEARNING ARABIC LANGUAGE AMONG ISLAMIC FINANCIAL STUDENTS - Ahmad Farid Fadhli Mustafa; Muhammad Anas Al Muhsin (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The issue of Arabic language proficiency among students of Higher Education Institutions (HEIs) is a concern as the majority of students are still poor at mastering and understanding Arabic terms. The Arabic language learning and teaching scenario are based solely on the basic courses taken to qualify for the graduation process. The purpose of this study is to identify the Arabic language learning needs among Islamic Finance students in USAS. The study was a public survey of 60 undergraduate students in Islamic Finance using a self-administered questionnaire conducted by a researcher who has been certified by an expert in the field. The research questionnaire was divided into 3 main sections: identifying the respondents’ background, students’ knowledge of the Arabic language and their Arabic language learning needs. This data is analyzed using descriptive statistics of frequency and percentage only. The findings showed that Arabic knowledge of Islamic finance course information had the highest frequency and percentage of n = 35; 58.3%. Whereas the Arabic language learning needs show the highest frequency and percentage are related to the manual or module of learning Arabic for n = 45; 75%. In conclusion, the findings of this study are proposed as a guide to developing the development of Arabic language modules for a more robust study in Malaysian HEIs.